Analisis Segmenting, Targeting, dan Positioning (STP) Tabungan Haji pada Bank Nagari Cabang Ujung Gading, Pasaman Barat, Sumatera Barat - Rahma Alya; Rahmi Isriani (ARZUSIN, 2026)
The segmenting, targeting, and positioning (STP) marketing strategy is an important approach to enhancing the competitiveness of Islamic banking products, including Hajj savings. Although the STP strategy has been widely examined in the field of marketing, research on its implementation in the Tahari Mabrur Hajj Savings product at Bank Nagari Ujung Gading Branch remains limited. This study aimed to analyze the implementation of segmenting, targeting, and positioning strategies and to identify constraints in marketing the Tahari Mabrur Hajj Savings product at Bank Nagari Ujung Gading Branch. The study employed a qualitative approach with a descriptive field study design. Informants were selected through purposive sampling and included the Deputy Branch Manager, marketing staff, and Tahari Mabrur Hajj Savings customers. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which included data reduction, data display, and conclusion drawing. The results showed that Bank Nagari Ujung Gading Branch had implemented the STP strategy, but its implementation had not yet been optimal. The segmenting strategy was still dominated by geographic and demographic segmentation, whereas psychographic and behavioral segmentation had not been utilized optimally. The targeting strategy was directed toward Muslim communities with the financial capacity and intention to perform the Hajj pilgrimage, whereas the positioning strategy was developed through the image of a product that is secure, reliable, and compliant with Sharia principles. The main constraints in product marketing included limited promotional media, suboptimal market segmentation, and increasing competition among financial institutions. These findings extend the application of the STP concept in the context of Islamic banking marketing and emphasize the importance of developing more effective market segmentation and promotional media. In practical terms, the results can serve as a basis for Bank Nagari Ujung Gading Branch in formulating a more focused and competitive marketing strategy for the Tahari Mabrur Hajj Savings product that is aligned with the characteristics of prospective customers.